Postingan Instagram Sebagai Media Self Disclosure Mahasiswa Komunikasi dan Penyiaran Islam UIN Jambi - Dwi Intan Rahayu; Ardiansyah Ardiansyah; Muhammad Al-hafiz; Herri Novealdi (Jurnal Perspektif, 2023)
This research discusses the use of the Instagram social media platform by students of the Islamic Communication and Broadcasting Program (KPI) at UIN Jambi as a means of engaging in self-disclosure. The study draws upon the Johari Window theory to explain the level of openness exhibited by students in using Instagram. Data were collected through interviews with five informants who were active Instagram users and students of the KPI program at UIN Jambi. The findings reveal that students of KPI UIN Jambi actively use Instagram and utilize various features such as posts, reels, and stories. They employ Instagram as a source of information, seek inspiration, enhance their knowledge, and connect with new individuals. In the context of the Johari Window, Instagram enables students to expand their open self by sharing daily activities and receiving attention and feedback from their followers. However, students also acknowledge the limitations of self-disclosure and maintain their hidden self by refraining from sharing overly sensitive or irrelevant personal aspects. They also experience a blind self in which others' interpretations of their content may differ from their intended messages. Lastly, there is an unknown self, wherein they occasionally post something unintended and swiftly remove it.